The Inevitable Pressure Between Progression And Knowledge Impartation - Mohammed Xolile Ntshangase; Segooa, Mapule Yvone; Ntshangase, Shonisani Cydna (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
It has always been the case that teachers must produce a higher pass-rate to the managers. Due to this expectation, at some point lazy students get to rest well knowing that the teacher will have to make a plan to push them to pass. This has many implications like; (a) a teacher has to create intellectually weak assessments, (b) adjust the marks after giving assessments and students failed, or (c) having to account to the managers after having a low pass-rate. The serious issue with this situation is the harsh approach of the management towards the teacher who obtained a low pass-rate. S/he gets viciously blamed and confronted as if there cannot be any other factors that lead to a low pass-rate. The management’s approach is commonly bias towards supporting the learners at the unfair exposition of the teacher. Research methods include document analysis and semi-structured interviews within the education sector. Results of this study show that this kind of approach towards education management creates a power exercise dilemma between students and teachers. This victimization of teachers by students after the bias approach to the issue of lower pass-rate is even getting emphasized by some policies like progression policy that says ‘no student must repeat the class 2 times. This pressurizes the teacher as it makes it seem like it is a guaranteed fact that the student will improve after failing once. It is the conclusion of this paper that such misguided philosophy of the educational management must be put under logical scrutiny and be corrected for quality teaching and assessment. Using analytic theory, this qualitative study explores different ways in which low pass-rate issue can be addressed without creating power exercise dilemma which ends up supporting students’ laziness and protests after obtaining low pass-rate.